Numerical prediction of the effective thermal conductivity of perforated hollow sphere structures - Hosseini, S. M. H. (Scitec Publications Ltd., 2008)
This paper investigates the thermal properties of a new type of hollow sphere structures. For this new type, the sphere shell is perforated by several conical holes in order to open the inner sphere volume. The effective thermal conductivity of perforated sphere structures in a primitive cubic arrangement is numerically evaluated for different material combinations and compared to sphere structures without perforation.